A Social Force Model for Pedestrians' Movements Affected by Smoke Spreading. (16th November 2020) - Makmul, J.
Abstract : A social force (SF) model is proposed to simulate the egress of pedestrians while smoke is spreading. The advection-diffusion with source term is used to describe the propagation of smoke. It is incorporated into the SF model. The navigation field in our model is determined by the negative gradient of the solution of the Eikonal equation. It depends on the pedestrian and smoke density. Numerical experiments are performed in a room with multiple exits, and their results are shown.